Open Standard Query Interface for Geospatial Databases in OSA /Parlay - Masenya, Lebogang Kenneth (My University, 2006)
Telecommunication networks have evolved from voice only single service networks to multimedia networks providing bearer services such as voice, data and video transportation. Moreover, these networks, collectively called Next Generation Networks (NGNs), enable rapid creation, deployment and management of advanced services in an efficient manner. However, the initial business model of telcos was to internally develop and provide these advanced services to customers. In this monopolized environment, service development is driven by technological availability rather than customer demands. Furthermore, vendor specific network elements prohibit the development of re-useable service components, which in turn increases the time-to-market of services. Deregulation and advances in Distributed Computing Systems (DCSs) are driving towards open networks and rapid service delivery. Third party Application Service Providers (ASPs) are envisioned to develop and supply the services, with the telco providing bearer services. The use of softswitch architectures such as Open Service Access (OSA) / Parlay (OSA / Parlay) in an open NGN environment abstract services from core network elements through its Application Programming Interface (API). Services are thus decoupled from vendor and protocol specific network equipment and can be provided across a plethora of network architectures. One major advantage of NGN is the ability to provide bearer service in a mobile environment. Location Based Services (LBSs) are envisaged to be an important class of services provided in the NGN environment. For an LBS service to be complete, a geospatial database is necessary to provide location information. This report documents the design and implementation of a Geospatial Data Access Service Capability Feature (GDASCF) as an extension to the OSA / Parlay gateway. The GDASCF encapsulates necessary APIs that offer uniform access to query geospatial databases. One key component of the design is the realization of the Adapter layer which adapts function calls to an appropriate Database Management System (DBMS). The introduction of the GDASCF and Adapter layer provides a solution which results in flexible and rapid service creation.
Student Number :9600874K - MSc research report - School of Electrical Engineering - Faculty of Engineering and the Built Environment
Keywords: OSA; Parlay; GJS; geospatial; SCF; APJ; gateway